1989
DOI: 10.1161/01.cir.79.5.1043
|View full text |Cite
|
Sign up to set email alerts
|

Direct vasoconstriction and endothelium-dependent vasodilation. Mechanisms of acetylcholine effects on coronary flow and arterial diameter in patients with nonstenotic coronary arteries.

Abstract: An endothelium-dependent vasodilator response to acetylcholine has been described recently in patients with coronary artery disease. Those studies determined responses only of large epicardial arteries. Our study was designed to determine the integrated effects of acetylcholine on epicardial diameter, coronary flow, and vascular resistance. Patients (n=64) with nonstenotic epicardial coronaries underwent coronary angiography with simultaneous recording of coronary flow velocity using a 3F subselective Doppler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2
6

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(66 citation statements)
references
References 26 publications
3
55
2
6
Order By: Relevance
“…21 Hodgson, using methylene blue (an inhibitor of the action of EDRF) suggested that acetylcholine is capable of releasing EDRF in humans. 22 In clinical studies, intracoronary acetylcholine infusion constricts coronary arteries when there is angiographic evidence of atherosclerosis in the studied vessel.10-12 However, controversy exists regarding the response of "normal" coronary arteries.101113 Furchgott1 described the endothelium-dependent vasomotor response of arteries to acetylcholine in vitro throughout a specific dose range. Variation in dose and rate of acetylcholine infusion may account in part for the reported heterogenous response in patients.…”
Section: Diameter Responsesmentioning
confidence: 99%
“…21 Hodgson, using methylene blue (an inhibitor of the action of EDRF) suggested that acetylcholine is capable of releasing EDRF in humans. 22 In clinical studies, intracoronary acetylcholine infusion constricts coronary arteries when there is angiographic evidence of atherosclerosis in the studied vessel.10-12 However, controversy exists regarding the response of "normal" coronary arteries.101113 Furchgott1 described the endothelium-dependent vasomotor response of arteries to acetylcholine in vitro throughout a specific dose range. Variation in dose and rate of acetylcholine infusion may account in part for the reported heterogenous response in patients.…”
Section: Diameter Responsesmentioning
confidence: 99%
“…Infusion of acetylcholine (ACh) in vivo in the coronary circulation revealed that ACh has a dual action, causing vasodilatation at low and vasoconstriction at high doses in the baboon (Van Winkle & Feigl, 1989;Knight et al, 1991), cattle and man (Hodgson & Marshall, 1989;Knight et al, ' Author for correspondence. (Van Winkle & Feigl, 1989;Knight et al, 1991), and only vasoconstriction in the porcine coronary circulation (Kawamura et al, 1989;Cowan & McKenzie, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…However, the vascular response to ACh may not be caused solely by the release of endothelium-derived NO, but may also involve direct smooth muscle constriction; that is, the net effect of ACh on the human coronary vasculature is the result of a combination of both effects. 6 Therefore, as far as the 3 patients with HCM and coronary vasospasm are concerned, it is plausible that the AChinduced coronary vasocontractions were caused by the impaired release of endothelium-derived NO or enhanced direct smooth muscle constriction, or a combination.…”
Section: Coronary Vasomotor Responses To Achmentioning
confidence: 99%
“…4,5 However, ACh is not only an endothelium-dependent vasodilator, but can also serve as a potent vasoconstrictor in human coronary arteries. 6 The net vascular bed response to ACh depends on the interplay between both effects. Little information is currently available regarding coronary endothelial function in patients with HCM.…”
mentioning
confidence: 99%